2018
DOI: 10.2339/politeknik.417756
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Entropy Generation for Ag-MgO/Water Hybrid Nanofluid Flow through Rectangular Minichannel by Using Artificial Neural Network

Abstract: The convective heat transfer and entropy generation characteristics of Ag-MgO/water hybrid nanofluid flow through rectangular minichannel were numerically investigated. The Reynolds number was in the range of 200 to 2000 and different nanoparticle volume fractions were varied between  = 0.005 and 0.02. In addition, Artificial Neural Network was used to create a model for estimating of entropy generation of Ag-MgO/water hybrid nanofluid flow. As a result, it was found that the convective heat transfer coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
4
8
0
Order By: Relevance
“…The incremental trend at high Re was also higher than the incremental trend at low Re. This tend of results gives a good agreement with the trend obtained 38,69 . At Re higher than 200, the highest values of Ṡ� gen,total were for the ternary hybrid nanofluid followed by the binary hybrid nanofluid and water.…”
Section: Frictional Entropy Generationsupporting
confidence: 90%
“…The incremental trend at high Re was also higher than the incremental trend at low Re. This tend of results gives a good agreement with the trend obtained 38,69 . At Re higher than 200, the highest values of Ṡ� gen,total were for the ternary hybrid nanofluid followed by the binary hybrid nanofluid and water.…”
Section: Frictional Entropy Generationsupporting
confidence: 90%
“…López et al [15] found that Nu increases on the hot wall of a porous microchannel and decreases on its cold wall by increasing φ and injecting the flow. Jalali and Karimipour [16] reported that Nu increases with Re and φ. Convective heat transfer and entropy generation of Ag-MgO/water hybrid nanofluid in microchannel are discussed by Uysal and Korkmaz [17]. They found that heat transfer increases as the volume fraction of hybrid nanofluid increases.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the heat transfer rate and increasing values of NP had a proportionate relationship. Uysal et al 23 concluded that the Nusselt number increases linearly with increasing Reynolds number.…”
Section: Resultsmentioning
confidence: 99%
“…22 The researchers showed that incorporating NP into a base fluid increases heat transfer. Uysal and Korkmaz 23 numerically studied the entropy generation of a hybrid nanofluid flow through a rectangular mini-channel. The results reveal that the convective heat transfer and S tot of the Ag-MgO/water hybrid nanofluid increased when the NP concentration increased.…”
mentioning
confidence: 99%